Estimating Long-Term Survival of Adults with Philadelphia Chromosome-Negative Relapsed/Refractory B-Precursor Acute Lymphoblastic Leukemia Treated with Blinatumomab Using Historical Data. Issue 1 (January 2017) - Barlev, Arie; Lin, Vincent; Katz, Aaron; Hu, Kuolung; Cong, Ze; Barber, Beth
Abstract Introduction Blinatumomab is a bispecific T cell-engaging antibody construct indicated for adult patients with relapsed/refractory (R/R) Ph(−) B-precursor acute lymphoblastic leukemia (ALL), an aggressive disease with poor prognosis. A phase 2 single-arm clinical study showed that 43% of patients achieved CR/CRh within two cycles and approximately 20% of patients receiving blinatumomab were still alive after 2 years. Methods The objective of the current analysis was to estimate long-term survival of patients receiving blinatumomab beyond the observed time period in the clinical study using a large historical observational dataset. Conditional survival probabilities of blinatumomab-treated patients beyond month 60 were assumed to be the same as the US general population. Results At month 60, the estimated proportion of blinatumomab-treated patients alive was more than double that of historical patients (12.6% vs 5.4%). The mean overall survival was 76.1 months for blinatumomab patients and 39.8 months for historical patients. Sensitivity analyses including additional follow-up data from the clinical study showed consistent results. Conclusions These findings suggest that blinatumomab provides substantial overall survival benefit to patients with (R/R) Ph(−) B-precursor ALL compared with salvage chemotherapy. Funding Amgen. Trial Registration ClinicalTrials.gov identifier NCT01466179 and NCT02003612.